2008
DOI: 10.1152/japplphysiol.00152.2007
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of nocturnal sustained hypoxia and obesity additively increases cardiac apoptosis

Abstract: . The coexistence of nocturnal sustained hypoxia and obesity additively increases cardiac apoptosis. J Appl Physiol 104: 1144-1153, 2008. First published January 17, 2008 doi:10.1152 doi:10. /japplphysiol.00152.2007 nocturnal sustained hypoxia during sleeping time has been reported in severe obesity, but no information regarding the cardiac molecular mechanism in the coexistence of nocturnal sustained hypoxia and obesity is available. This study evaluates whether the coexistence of nocturnal sustained hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Lee and coworkers [35] suggested that ZF rats exhibited reduced LVDs and LVDd compared to their lean littermates; however, the fractional shortening was not different amongst the two groups. The improvement in LVDs and fractional shortening induced by Provinols™ was also accompanied with an increase in fraction of ejection and cardiac output, illustrating an improvement in systolic function.…”
Section: Discussionmentioning
confidence: 93%
“…Lee and coworkers [35] suggested that ZF rats exhibited reduced LVDs and LVDd compared to their lean littermates; however, the fractional shortening was not different amongst the two groups. The improvement in LVDs and fractional shortening induced by Provinols™ was also accompanied with an increase in fraction of ejection and cardiac output, illustrating an improvement in systolic function.…”
Section: Discussionmentioning
confidence: 93%
“…M-mode echocardiographic examination was performed using a 14-MHz linear transducer via parasternal long axis approach (Lee et al 2008). Using the M-mode image, right ventricular inner-distance diastole (RV-D), interventricular septum in diastole (IVS-D), interventricular septum in systole (IVS-S), LV inner-distance diastole (LV-D), LV innerdistance systole (LV-S), LV posterior wall in diastole (LVPW-D), LV posterior wall in systole (LVPW-S), LV mass and chamber volume in diastole (LV vol-D), and chamber volume in systole (LV vol-S), and LV ejection fraction (LV-EF) were measured by American Society of Echocardiography guidelines.…”
Section: Echocardiographymentioning
confidence: 99%
“…These findings reiterate the interdependency of cardiac and respiratory functions [119]. Lee et al [122] also shed some light on the mechanisms of obesity-associated cardiomyopathy by using these animals. They evaluated the cumulative effect of obesity and nocturnal hypoxemia on cardiomyocyte apoptosis and showed that whole-heart weight, left ventricular weight, abnormal myocardial architecture, and TUNEL-positive apoptotic cells, as well as the activity of cardiac Fas-dependent and mitochondria-dependent apoptotic pathway, were significantly increased in the obese group or sustained nocturnal hypoxia group.…”
Section: The Natural Model Of Sleep-disordered Breathingmentioning
confidence: 63%
“…The FasR is also known as CD95, Apo-1, and tumor necrosis factor receptor superfamily member 6, which is located on chromosome 10 in humans and 19 in mice [124]. These changes were also accompanied by decreases in antiapoptotic protein Bc12 levels and Bid, and increases in Fas, FADD, proapoptotic protein Bad, BNIP3, cytosolic cytochrome c, activated caspase-8, activated caspase-9, and activated caspase-3 [122]. A syndrome of central sleep apnea, characterized by pauses of diaphragmatic activity, has also been reported in several albino rat strains, including Sprague-Dawley, Fischer-344, Wistar-Kyoto, and spontaneously hypertensive rats (SHR) [125][126][127][128].…”
Section: The Natural Model Of Sleep-disordered Breathingmentioning
confidence: 99%